2018
DOI: 10.2196/preprints.10485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How did Ebola Information Spread on Twitter: Broadcasting or Viral Spreading? (Preprint)

Abstract: Background: It has been argued that information and emotions towards public health issues could spread widely through online social networks. Although aggregate metrics on the volume of information diffusion are available, we know little about how information spreads on online social networks. For example, health information could be transmitted from one to many (i.e. broadcasting), which is similar to how traditional mass media passes information to the general public. Health information could also be transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Mc-Court et al (2018) found in their high-resolution simulations that indeed structures much larger than l shatter fragment, while smaller clouds do not. Recently, other groups have claimed to confirm this results in three dimensions and with magnetic fields (Liang & Remming 2018;Sparre et al 2018). The ratio between l shatter and our survival length scale r cl,crit is given by (cf.…”
Section: Numerical Convergence; Connection To 'Shattering'mentioning
confidence: 58%
See 1 more Smart Citation
“…Mc-Court et al (2018) found in their high-resolution simulations that indeed structures much larger than l shatter fragment, while smaller clouds do not. Recently, other groups have claimed to confirm this results in three dimensions and with magnetic fields (Liang & Remming 2018;Sparre et al 2018). The ratio between l shatter and our survival length scale r cl,crit is given by (cf.…”
Section: Numerical Convergence; Connection To 'Shattering'mentioning
confidence: 58%
“…We then scaled the density so that the mean density contrast is given by χ. A similar procedure was also followed by Schneider & Robertson (2017) and Liang & Remming (2018) to generate non-spherical initial conditions. Figure 12 shows the mass and velocity evolution in the upper and lower panel, respectively.…”
Section: Non-spherical Setupmentioning
confidence: 99%
“…Research on maximizing impressions and engagements on social media has exploded in recent years [30][31][32][33][34]. There are two main sets of features that have been examined: 1) the content of the message itself, including embedded content and linguistic factors; and 2) account-specific features, including number of followers/subscribers, position, institutional context, and frequency of posting.…”
Section: Maximizing Engagement On Social Mediamentioning
confidence: 99%